2012
DOI: 10.1182/blood-2011-10-383752
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hedgehog in hematologic malignancy

Abstract: The Hedgehog pathway is a critical mediator of embryonic patterning and organ development, including hematopoiesis. It influences stem cell fate, differentiation, proliferation, and apoptosis in responsive tissues. In adult organisms, hedgehog pathway activity is required for aspects of tissue maintenance and regeneration; however, there is increasing awareness that abnormal hedgehog signaling is associated with malignancy. Hedgehog signaling is critical for early hematopoietic development, but there is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
101
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 99 publications
1
101
0
Order By: Relevance
“…4 Kobune et al showed activation of Hh signaling in primary CD34 + blasts from AML 5 and, recently, these same authors reported the expression of Indian Hh (IHH) and Smoothed (SMO) in AML-and MDS-derived CD34 + cells. 6 Here, we characterize expression of central components of the Hh pathway in the bone marrow (BM) of MDS patients.…”
mentioning
confidence: 96%
“…4 Kobune et al showed activation of Hh signaling in primary CD34 + blasts from AML 5 and, recently, these same authors reported the expression of Indian Hh (IHH) and Smoothed (SMO) in AML-and MDS-derived CD34 + cells. 6 Here, we characterize expression of central components of the Hh pathway in the bone marrow (BM) of MDS patients.…”
mentioning
confidence: 96%
“…[9][10][11][12]. Gli1 is a positive effector of signaling, Gli3 is predominantly a transcriptional inhibitor, and Gli2 can function in both roles (9)(10)(11)(12). Smo signals to a cytoplasmic complex that releases Gli1, which translocates to the nucleus where it activates the Hedgehog target genes (9,10,13).…”
Section: Introductionmentioning
confidence: 99%
“…The Hedgehog signaling pathway consists of 3 closely related ligands, Sonic Hedgehog (Shh), Indian Hedgehog (Ihh), and Desert Hedgehog (Dhh), that can each bind to the transmembrane protein Patched (PTCH; refs. [8][9][10]. Upon ligand binding, PTCH inhibition of the positive effector Smoothened (Smo) is released and leads to production of activating forms of glioma-associated oncoproteins 1-3 (Gli1-3; refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…kinase, PTEN, p53) and self-renewal (Wnt, Hedgehog, Notch) pathways [2][3][4][5][6][7][8][9].Furthermore, the therapy is highly toxic and poorly tolerated, particularly by older patients. Therefore, the development of novel therapeutic agents and strategy is in an urgent need for improving outcomes in patients with AML.…”
mentioning
confidence: 99%